Kualitas Tidur Pada Lansia Penderita Hipertensi Di Masa Pandemi Covid-19 - Ramadhani, Yossy - (Universitas Aufa Royhan, 2022)
Elderly people with hypertension have the greatest risk of exposure to Covid-19 and the highest death due to Covid-19 based on comorbidities. As a result of these conditions, many elderly people feel worried that it will cause the elderly to experience sleep disorders which will affect the quality of sleep of the elderly. This study aims to look at the picture of sleep quality in the elderly with hypertension during the Covid-19 pandemic. This study uses a descriptive design. The research was conducted in the Rejosari Public Health Center with 133 samples taken by purposive sampling technique. The measuring instrument used is the PSQI (Pittsburgh Sleep Quality Index) questionnaire which has been tested for validity and reliability into a KTlC-19 questionnaire. The analysis used is univariate analysis. The results of this study indicate that as many as 75 people (56.4%) elderly with hypertension have poor sleep quality. It can be concluded that hypertension sufferers have poor sleep quality due to their hypertension condition and the Covid-19 pandemic condition which has a bad impact, causing a decrease in sleep quality in the elderly. It is expected for the elderly to be able to manage sleep well and avoid risk factors that can cause sleep quality disorders.